"Republicanism": a grounding concept for the American Revolution?. Issue 1 (2nd January 2023) - de Bolla, Peter
ABSTRACT: This essay revisits the long-standing debate concerning the sources for the underlying political beliefs and commitments held by the "founding generation, " those colonists who came to the conclusion that separation from the mother country was necessary and inevitable. It uses a mixed mode of enquiry and analysis, blending standard close reading of texts with computer-aided inspection of the archive at scale. It seeks to clarify the extent to which a set of political assumptions and theories widely assumed to be gathered under the rubric of "republicanism" could have shaped the thinking of this founding generation. Given that the term "republicanism" was very infrequent until the last decade or so of the eighteenth century, the essay proposes ways of interrogating the historical formation of concepts for which no label can be easily discerned. Following the consideration of some candidate terms or phrases that might, at the time of the American Revolution, have effectively been hosts for the political idea of "republicanism, " the essay arrives at the conclusion that the founding generation reimagined the role that "republicanism" had played in their thinking at the time.